2021
DOI: 10.1108/bij-10-2020-0545
|View full text |Cite
|
Sign up to set email alerts
|

Association between fund attributes and fund's performance: a panel data approach

Abstract: PurposeThe present study tries to explore the various fund attributes that influence the mutual fund performance. Further, study examined the effect of mutual fund attributes namely, Net Asset Value (NAV), Portfolio turnover ratio (PTR), fund size (AUM), expense ratio (ExpR) and fund age (Age) on mutual fund's performance using gross return and risk-adjusted performance measures.Design/methodology/approachThe study evaluated balanced panel data (short panel) comprising 81 Indian equity mutual fund schemes for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Prior studies demonstrated several determinants of the financial performance of mutual funds. Specifically, the performance of mutual funds was positively affected by the portfolio concentration (Fulkerson and Riley, 2019), the net asset value (Singh and Tandon, 2021) and teamwork (multitasking teams) (Chen et al , 2020), whereas it was negatively affected by the portfolio turnover ratio, the asset under management, the age (Singh and Tandon, 2021), the managerial multitasking (Chen et al , 2020) and the cultural distant investments (Tanos, 2022).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Prior studies demonstrated several determinants of the financial performance of mutual funds. Specifically, the performance of mutual funds was positively affected by the portfolio concentration (Fulkerson and Riley, 2019), the net asset value (Singh and Tandon, 2021) and teamwork (multitasking teams) (Chen et al , 2020), whereas it was negatively affected by the portfolio turnover ratio, the asset under management, the age (Singh and Tandon, 2021), the managerial multitasking (Chen et al , 2020) and the cultural distant investments (Tanos, 2022).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%